Two new rock-inhabiting species of Cyphellophora from karst habitats in China - Sun, Wei; Liu, Bingjie; Fu, Rong; Liu, Xingzhong; Xiang, Meichun (Phytotaxa, 2019)
During survey on rock-inhabiting fungi from karst habitats in Guizhou, China, two new species in Cyphellophora were discovered and identified. Phylogenetic analysis based on combined sequences of the nuclear large subunit (nucLSU) and internal transcribed spacer (ITS) region of ribosomal DNA revealed that the tested isolates, clustered into two clades that well affiliated in the genus of Cyphellophora. Morphological characteristics were also supported the estabolishment of the new species. Herewith Cyphellophora botryose sp. nov. and Cyphellophora guizhouensis sp. nov. were described and their differences from closely related species were discussed.